2023
DOI: 10.7759/cureus.44922
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Mechanisms of Pulsed Radiofrequency for Pain Treatment

Jonathan De la cruz,
Daniel Benzecry Almeida,
Mayara Silva Marques
et al.

Abstract: Pulsed radiofrequency is a well-documented treatment option for multiple painful conditions where pulses of energy are delivered close to neural elements. Since its earliest adoption, this technique has gained increasing acceptance as a minimally invasive procedure, and new applications are evolving. Studies have shown microscopic and biochemical changes that reflect beneficial effects; however, the exact mechanism of action is not yet completely understood. To redress this paucity, 11,476 articles of scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…A computational model has suggested that very high peak power pulses of extremely short duration can induce potentially injurious high tensile stresses comparable with but different from football blunt head impacts . Of note, the US Food and Drug Administration has approved transcranial magnetic stimulation for the treatment of major depression and obsessive-compulsive disorder, while research continues in the use of pulsed radiofrequency and pulsed magnetic fields for inducing electric currents in the brain as treatment for other disorders . Similarly, low-intensity focused ultrasound is understood to induce transient activation of ion channels and transient opening of the blood-brain barrier, depending on the pulsing scheme, and may prove useful for treatment of epilepsy, amyloid-associated disease, pain, and psychiatric disorders …”
mentioning
confidence: 99%
“…A computational model has suggested that very high peak power pulses of extremely short duration can induce potentially injurious high tensile stresses comparable with but different from football blunt head impacts . Of note, the US Food and Drug Administration has approved transcranial magnetic stimulation for the treatment of major depression and obsessive-compulsive disorder, while research continues in the use of pulsed radiofrequency and pulsed magnetic fields for inducing electric currents in the brain as treatment for other disorders . Similarly, low-intensity focused ultrasound is understood to induce transient activation of ion channels and transient opening of the blood-brain barrier, depending on the pulsing scheme, and may prove useful for treatment of epilepsy, amyloid-associated disease, pain, and psychiatric disorders …”
mentioning
confidence: 99%